'HeART of Stroke (HoS)', a community-based Arts for Health group intervention to support self-confidence and psychological well-being following a stroke: protocol for a randomised controlled feasibility study. Issue 8 (4th August 2015) - Ellis-Hill, Caroline; Gracey, Fergus; Thomas, Sarah; Lamont-Robinson, Catherine; Thomas, Peter W; Marques, Elsa M R; Grant, Mary; Nunn, Samantha; Cant, Robin P I; Galvin, Kathleen T; Reynolds, Frances; Jenkinson, Damian F
Abstract : Introduction: Over 152 000 people in the UK have strokes annually and a third experience residual disability. Low mood also affects a third of stroke survivors; yet psychological support is poor. While Arts for Health interventions have been shown to improve well-being in people with mild-to-moderate depression post-stroke, their role in helping people regain sense of self, well-being and confidence has yet to be evaluated. The main aim of this study is to explore the feasibility of conducting a pragmatic multicentre randomised controlled trial to assess the effectiveness and cost-effectiveness of an Arts for Health group intervention ('HeART of Stroke' (HoS)) for stroke survivors. HoS is a 10-session artist-facilitated group intervention held in the community over 14 weeks. It offers a non-judgemental, supportive environment for people to explore sense of self, potentially enhancing well-being and confidence. Methods and analysis: Sixty-four people, up to 2 years post-stroke, recruited via secondary care research staff or community stroke/rehabilitation teams in two UK centres will be randomised to either HoS plus usual care or usual care only. Self-reported outcomes, measured at baseline and approximately 5 months postrandomisation, will include stroke-related, well-being, mood, self-esteem, quality of life and process measures. Analyses will focus on estimating key feasibility parameters (eg, rates of recruitment, retention, intervention attendance). We will develop outcome and resource use data collection methods to inform an effectiveness and cost-effectiveness analysis in the future trial. Interviews, with a sample of participants, will explore the acceptability of the intervention and study processes, as well as experiences of the HoS group. Ethics and dissemination: National Health Service (NHS), Research and Development and University ethical approvals have been obtained. Two peer-reviewed journal publications are planned plus one service user led publication. Findings will be disseminated at key national conferences, local stakeholder events and via institutional websites. Trial registration number: ISRCTN99728983.